The mechanisms and consequences of haemodialysis induced acute cardiac injury - Burton, James O. (2009)
Patients on dialysis are subject to a hugely elevated risk of cardiovascular mortality. Incidence and prevalence of, and mortality and morbidity from heart failure is significantly higher in the haemodialysis population than the general population as a whole. This thesis describes research work focusing on the large scale haemodynamic changes that occur during haemodialysis and how they may negatively impact on the cardiovascular system.